Women’s Socio-Economic Autonomy and Fertility Behaviour: Evidence from the Nigeria Demographic and Health Survey 2018 - Amaegberi, A. Michael; Uzobo, Endurance (Social Science Research, 2022)
This study investigated the relationship between women’s socio-economic autonomy and fertility behaviour in Nigeria, using data from the 2018 Nigeria Demographic and Health Survey. The impact of changes in women’s age, number of children, place of residence, region, educational level, religion, wealth index, occupation status, and family context on fertility behaviour was studied. In 42,000 families, women aged 15 to 49 were chosen. Tables of frequency and percentage distributions were used to examine the characteristics of women. The chi-square results reveal a strong link between women’s reproduction desires and their autonomy dimensions. The results of the regression model indicate that women in the poorest households were three times (OR=3.828, CI=3.560-4.117) most likely to desire children more than the ideal number stipulated than those in the richest households.Women who did not have any formal education or training were eight times most likely (OR=8.724, CI=8.147-9.340) to have higher fertility relative to those with higher education or training. By implication, fertility will continue to rise among women with low literacy level.Thus, it was recommended that there is a need for increased empowerment programmes like informal skill acquisition training like fashion designing, computer literacy etc specifically targeted reproductive women. This will to a large extent improve their socio-economic status which will, in turn, give them some form of control over the decision on fertility.